Exploring Pain Empathy Among Doctors, Nurses and Patients: A Scoping Review - Zhou WQ; Gao YT; Zhang CR; Xing Y; Zhou LS; Luan W (Journal of Multidisciplinary Healthcare)
Wan-Qiong Zhou,1,* Yi-Tian Gao,2,* Cheng-Rui Zhang,3 Ying Xing,3 Lan-Shu Zhou,2 Wei Luan1 1Department of Nursing, Shuguang Hospital Affiliated With Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2College of Nursing, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 3College of Nursing, Shanghai Jiao Tong University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Luan, Department of Nursing, Shuguang Hospital affiliated with Shanghai University of Traditional Chinese Medicine, 528 Zhangheng Road, Shanghai, People’s Republic of China, Tel +86 15921317982, Email luanwei_shuguang@126.com Lan-Shu Zhou, College of Nursing, Shanghai University of Traditional Chinese Medicine, 1200 Cailun Road, Shanghai, People’s Republic of China, Tel +86 13761801446, Email zhoulanshu@hotmail.comPurpose: This review aims to systematically assess the existing body of research on pain empathy among healthcare workers and patients, with the goal of enhancing both understanding and clinical application.Methods: Studies were retrieved from seven databases: PubMed, EBSCO, The Cochrane Library, Embase, CBM, CNKI, and Wanfang, with a search date limit from database inception to September 13, 2024. Inclusion and exclusion criteria were established based on the PCCs (Population, Concept, Context, Study design) principle. The research was independently screened and summarized by two researchers. A pre-designed data extraction form was used for information extraction from the included studies.Results: A total of 4729 studies were initially identified, with 50 studies included after screening. The participants were categorized into six groups: pain patients, nurses, patients with neurological diseases, cancer patients, patients with psychiatric disorders, doctors, and medical students. The studies employed 75 distinct research tools, including the Empathy for Pain Scale (EPS), the Interpersonal Reactivity Index (IRI), pain empathy paradigms, and the Visual Analogue Scale (VAS), along with various detection technologies, such as functional magnetic resonance imaging (fMRI) and electroencephalography (EEG). Factors influencing pain empathy included psychological factors, individual traits, and social influences. Mechanistic studies explored the neural substrates of emotional empathy (anterior insula, anterior cingulate cortex, amygdala), cognitive empathy (precuneus and parietal-occipital junction), the relationship between emotional regulation and cognitive processing, and the synergistic interactions of multiple brain regions.Conclusion: This review offers a comprehensive overview of research on pain empathy among healthcare workers and patients, emphasizing its multidisciplinary nature and complexity. It provides theoretical foundations and outlines potential directions for future research, which may include the adoption of unified research standards, interdisciplinary collaboration, the application of advanced technologies, and cross-cultural studies to further advance the field of pain empathy.Keywords: pain empathy, healthcare worker, patient, scoping review